(untitled) (Research, Society and Development, 2020)
Heart failure is a chronic disease that compromises the patient’s quality of life, due to its symptoms, such as: tiredness/fatigue, exercise intolerance, orthopnea, paroxysmal nocturnal dyspnea. The aim of the present study was to intervene and assist in the treatment of Heart Failure patient with pharmacological and non-pharmacological approaches in order to improve the quality of life and patient compliance regarding the existing disease. Pharmaceutical consultations were carried out over a seven-month period with a patient that suffers from Heart Failure, resident of Umuarama-PR, treated at home. The SOAP method was adopted for the registration of consultations for later analysis, and the measurement of blood pressure was performed by the patient, using the HBPM method. For the analysis of interactions, the Micromedex database and the patient’s package leaflet were used.The patient had a significant decrease in his BP with the follow-up; however, he showed resistance to going to the doctor. After some guidance, the patient agreed to go to the consultation and he was diagnosed with Renal Failure and Prostatic Hyperplasia. It is concluded that pharmaceutical care can be an effective alternative in obtaining better clinical results and helps to improve the patient’s quality of life, since it can provide awareness of their health status and the need for the correct use of medications, making the most effective and safe treatment.